2020
DOI: 10.1002/jsfa.10692
|View full text |Cite
|
Sign up to set email alerts
|

Browning and quality management of pear fruit by salicylic acid treatment during low temperature storage

Abstract: BACKGROUND‘Patharnakh’ pear, a dominant cultivar in the Punjab province of India, has a shorter storage life as it matures during the hot and humid weather. Studies have reported that postharvest chemical treatments have a major role in improving the storage life of the fruit. In this study, the efficacy of different concentrations (1, 2, and 3 mmol L−1) of salicylic acid (SA), a well‐known signaling molecule, was explored to overcome browning and maintain the postharvest quality of the Patharnakh pear during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 38 publications
4
15
0
Order By: Relevance
“…Statistical significance was assessed at p = 0.05, and means were separated using Duncan's multiple range test. Correlation analysis was performed using a two-tailed Pearson's correlation test [32].…”
Section: Discussionmentioning
confidence: 99%
“…Statistical significance was assessed at p = 0.05, and means were separated using Duncan's multiple range test. Correlation analysis was performed using a two-tailed Pearson's correlation test [32].…”
Section: Discussionmentioning
confidence: 99%
“…Guan et al, [39] discovered no significant effect of salicylic acid on fruit firmness. According to Adhikary et al [40], salicylic acidtreated fruits demonstrated that SA application slowed the rate of weight loss.…”
Section: Fruit Firmness and Weight Lossmentioning
confidence: 99%
“…) in combination with calcium chloride (1.5 and 3 5%) effective in decreasing ethylene content and browning of fruit and thus increasing fruit quality during storage. According to Adhikary et al [40], the Salicylic acid-treated fruits exhibited slower oxidation of total phenol content by inhibiting PPO action and retaining total phenolic content, resulting in a lower incidence of browning.…”
Section: Alleviation Of Browningmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the maintenance of previous compounds in litchi was obtained by dipping fruits in 1 mM SA after harvest [ 14 ]. Moreover, papaya and pear fruits immersed in 2 mM SA after harvest showed higher ascorbic acid content, antioxidants, phenolic compounds, and carotenoids than a control treatment during cold storage [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%